Camp Washington Letters, - Meyers, Jacob A., 1855-1925
Letters from Jacob Allen Meyers of Meyers Falls, Washington to Otto Wollweber of Reardan. The letters discuss the location of Camp Washington and the location of the historical marker. In 1908, the Washington State Historical Society erected a historical marker, but many historians believed it was in the wrong place, including Meyers. The marker was changed in 1928.